Storage Protein Synthesis in Maize: II. Reduced Synthesis of a Major Zein Component by the Opaque-2 Mutant of Maize - Jones, Richard A. (1977)
Two zein proteins (Z1 and Z2) represent the majority of the protein synthesized during maize endosperm development. Undegraded membrane-bound polysomes isolated from normal maize synthesized these proteins when incubated in a cell-free protein-synthesizing system from wheat germ. The proteins synthesized in vitro were similar to authentic zein in ethanol solubility and electrophoretic mobility. Zein synthesis was associated with large size classes of membrane bound polysomes in normal maize. Membrane-bound polysomes isolated from developing kernels of opaque-2 mutant synthesized less total zein in vitro, and dramatically reduced incorporation into the Z1 component. The reduction in total zein corresponded to a 50% reduction in the level of membrane-bound polysomes in opaque-2, and the near absence of the large polysome size classes, which synthesized zein in normal maize. We concluded that the opaque-2 mutation results in a decreased “availability” of the zein mRNAs, reflected in a reduced level of membrane-bound polysomes.